Total neoadjuvant immunochemotherapy for proficient mismatch repair or microsatellite stable locally advanced rectal cancer - Li, Xing; Tang, Ligong; Cheng, Fangyuan; Xu, Yongchao (Frontiers in Immunology, 2025)
ObjectiveOur goal was to assess the efficacy of integrating PD-1 inhibitors with total neoadjuvant treatment (iTNT) in enhancing complete response (CR) rates and the propensity for watch-and-wait (WW) strategies in patients with proficient mismatch repair or microsatellite stable (pMMR/MSS) locally advanced rectal cancer (LARC).MethodsA retrospective analysis of data prospectively collected was performed. Enrolled patients were divided into Group SCRT-IC, which received short-course radiotherapy (SCRT) followed by six cycles of consolidation immunotherapy with capecitabine and oxaliplatin, or to Group IC-SCRT, which underwent two cycles of induction immunotherapy followed by SCRT and the remaining four cycles of chemotherapy. The primary endpoint was CR.ResultsA total of 141 patients were included (72 in Group SCRT-IC and 69 in Group IC-SCRT). At a median follow-up of 29 months, the CR rates were 55.6% in Group SCRT-IC and 53.6% in Group IC-SCRT. The pCR rates were reported at 50% for both groups. Seventeen patients in each group were treated with WW and remained disease-free. The most prevalent grade 3 to 4 toxicities were thrombocytopenia and neutropenia. The cCR rate was a little higher in Group SCRT-IC (56.9% compared to 53.6%), and the incidence of grade 3 to 4 thrombocytopenia was lower in Group SCRT-IC (24.2% vs. 33.9%).ConclusioniTNT regimen has significantly improved the CR rate for pMMR/MSS LARC compared to historical standards, with acceptable toxicity. The approach of prioritizing SCRT followed by immunotherapy is a promising strategy for definitive investigation in future studies.